Functional mitral stenosis after mitral valve repair for Type II dysfunction: determinants and impacts on long-term outcome. (27th February 2018) - Kawamoto, Naonori; Fujita, Tomoyuki; Fukushima, Satsuki; Shimahara, Yusuke; Kume, Yuta; Matsumoto, Yorihiko; Yamashita, Kizuku; Asakura, Koko; Kobayashi, Junjiro
Abstract: OBJECTIVES: This study was performed to analyse the impacts of functional mitral stenosis (MS) following mitral valve (MV) repair on late cardiac function and new onset of atrial fibrillation or survival. METHODS: We retrospectively reviewed 602 patients with mitral regurgitation who underwent MV repair for Type II dysfunction from 2001. Functional MS was diagnosed when the mean transmitral pressure gradient (MTPG) was ≥5 mmHg on postoperative echocardiography. We analysed preoperative and surgical risk factors for functional MS (MS group). We then compared long-term outcomes and late cardiac function over time between patients in the MS and no-MS groups using a mixed-effects model with repeated measures. RESULTS: On postoperative echocardiography, 51 patients had an MTPG of ≥5 mmHg (MS group) and 551 had an MTPG of <5 mmHg (no-MS group). Only the ring size was an independent predictor of MS (28.8 ± 2.1 mm in the no-MS group vs 28.0 ± 1.9 mm in the MS group, P  = 0.004). During follow-up, increases in the tricuspid regurgitation (TR) pressure gradient ( P RV-RA ) and TR severity over time were significantly greater in the MS group than in the no-MS group ( P RV-RA : 0.72 ± 0.16 vs 0.35 ± 0.17 mmHg per year, respectively, P  = 0.03; TR severity: 0.072 ± 0.014 vs 0.034 ± 0.015 per year, respectively, P  = 0.0113). Moreover, the 10-year rate of new onset of atrial fibrillation was significantly lower in the MS group than in the no-MS group (37.5% vs 16.9%, respectively; log-rank P  = 0.003). CONCLUSIONS: Annuloplasty using a small-sized ring in MV repair caused a postoperative high MTPG, which induced an elevation in the pulmonary artery pressure and residual TR grade and causing new onset of atrial fibrillation despite a competent MV.